Risk in Postgraduate Writing: Voice, Discourse and Edgework - Thesen, Lucia (Critical Studies in Teaching and Learning, 2023)
This paper brings writing into the contested space of research and knowledge-making in South Africa. An often hidden dimension of research is that it has to find expression in a written product, increasingly in English. This creates challenges for both students, who have developed writing identities in other domains, disciplines and languages, and also supervisors and journal editors who are gatekeepers for the making of new knowledge. In a competitive and uncertain climate where discourses of risk management play an increasingly important part, people tend to play it safe when it comes to writing, conforming to a narrow image of scientific writing. This has consequences for knowledge-making as students often set aside the experiences, allegiances and styles they have developed along the way. Drawing on data from an international publishing project on risk in academic writing, the paper explores dilemmas around the process of research writing. These instances make the contradictions and tensions faced by writers and gatekeepers central, highlighting the importance of voice and risk. Both voice and risk are explored experientially and theoretically, with the emphasis on the potentials of risk. The concept of risk, not as risk management, but as risk-taking, offers new ways of thinking about writing that brings the decisions that writers and readers make to the fore. A focus on risk has the potential to offer new understandings about the changing landscapes in which writers and readers weigh up their options against notions of what is ’normal’. Finally I suggest edgework as a productive concept that can take work on risk forward in both research and pedagogy.